2021
DOI: 10.3390/ijerph18063167
|View full text |Cite
|
Sign up to set email alerts
|

Informal Dementia Caregivers: Current Technology Use and Acceptance of Technology in Care

Abstract: (1) Background: Given the increased social isolation caused by the COVID-19 pandemic, the challenges faced by informal dementia caregivers have increased. An increasing use of technology, both in care and dementia clinical trials, depends upon caregivers’ abilities as a user. Accordingly, the aim of our study was to verify the current technology (smartphone and computer) use and acceptance in care, regarding socio-demographic variables; (2) Methods: Questionnaires were distributed to 102 dementia caregivers, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 35 publications
2
29
0
Order By: Relevance
“…Technology was also reported as a good informal support measure to connect socially with loved ones (Tam et al., 2021). Smartphone use and acceptance were seen as feasible regardless of age, however, computer use was negatively correlated with age (Wójcik et al., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Technology was also reported as a good informal support measure to connect socially with loved ones (Tam et al., 2021). Smartphone use and acceptance were seen as feasible regardless of age, however, computer use was negatively correlated with age (Wójcik et al., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…The gap in access to digital technologies, including wearable devices, can widen the already present health and health care disparities [2]. Evidence shows that the younger, more educated, wealthier, and tech-savvy adults are more likely to use wearables compared with older adults, those with lower education and income, and non-tech-savvy individuals [21,28,48]. Farivar et al [49] explored the extent to which factors were associated with the adoption of wearable devices among older adults by conducting a mixed methods study and found their perceived complexity in using wearable devices as a barrier to adoption.…”
Section: Principal Findings and Implications For Policy And Practicementioning
confidence: 99%
“…Another study presents a qualitative and quantitative analysis on the use and acceptance of technology in caregivers [ 3 ]. This study reveals that computer use decreases with age.…”
Section: Related Workmentioning
confidence: 99%
“…There is no doubt that during the COVID-19 pandemic PwD and their caregivers were particularly vulnerable considering their mental-health and physical health [ 3 ]. Recent studies show that the elderly’s mental health was affected by isolation, their ability to live independently was hampered, provoking in some cases depression in the PwD and exhaustion in care providers [ 3 ].…”
Section: Introductionmentioning
confidence: 99%